2019
DOI: 10.48550/arxiv.1911.09377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The asymptotics of the clustering transition for random constraint satisfaction problems

Louise Budzynski,
Guilhem Semerjian

Abstract: Random Constraint Satisfaction Problems exhibit several phase transitions when their density of constraints is varied. One of these threshold phenomena, known as the clustering or dynamic transition, corresponds to a transition for an information theoretic problem called tree reconstruction. In this article we study this threshold for two CSPs, namely the bicoloring of k-uniform hypergraphs with a density α of constraints, and the q-coloring of random graphs with average degree c. We show that in the large k, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…9), an observation that we also made for the other values of b we investigated. We have given analytical arguments in [44] that indeed the plateau value of m n is exactly equal to 1 at γ d for the uniform measure, our numerical results suggest that this remains true when (b, ǫ) = (1, 0), even if we do not have analytical support for this assumption in the general case.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…9), an observation that we also made for the other values of b we investigated. We have given analytical arguments in [44] that indeed the plateau value of m n is exactly equal to 1 at γ d for the uniform measure, our numerical results suggest that this remains true when (b, ǫ) = (1, 0), even if we do not have analytical support for this assumption in the general case.…”
Section: Resultsmentioning
confidence: 70%
“…This Section being rather long and technical we give here, for the convenience of the reader, the main ideas and explain the organization of the forecoming computation, which is the generalization of the one we presented in [44] for the uniform measure. We will focus on the particular form of the function ψ(p) defined in (6), with the two parameters b and ǫ, and start in Sec.…”
Section: Large K Asymptoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we build upon our previous works [39,44] and generalize them to obtain two main new results. We first introduce a more generic way of weighting the different solutions of an instance of the hypergraph bicoloring problem, that extends the one presented in [39] and incorporates interactions between variables belonging to different hyperedges, and shows that for finite k it allows a further increase of the dynamic threshold α d .…”
Section: Introductionmentioning
confidence: 91%
“…As a matter of fact the large k behavior of α d is a rather involved asymptotic expansion, even for the uniform measure, and until recently only relatively loose bounds on the asymptotic behavior of α d were known [41][42][43]. We considered this specific problem in [44] and found that the clustering threshold occurs on the scale α ∼ 2 k−1 ( ln k + ln ln k + γ)/k with γ constant, and more precisely that for the uniform measure γ d,u ≈ 0.871, which falls into the range allowed by the previous bounds [41][42][43].…”
Section: Introductionmentioning
confidence: 99%